Legal Analysis of Handover Report (BAST) Clauses in Indonesian Government Hospital Construction Contracts - Rudy Hartono; Sri Astutik; Nur Handayati; Fitri Ayuningtyas (Penerbit Goodwood, 2026)
Purpose: This study aims to analyze the legal framework, contractual structure, legal compliance, and potential risks arising from the implementation of the Handover Report (Berita Acara Serah Terima/BAST) clause in the Ministry of Health Vertical Hospital Construction Project in Surabaya, Indonesia.Research Methodology: The study employs an empirical legal research approach with a socio-legal perspective. Data were collected through document analysis, in-depth interviews, and observations involving key project stakeholders. The data were analyzed qualitatively using NVivo 12 Plus to identify dominant themes, patterns, and legal issues related to BAST implementation.Results: The findings indicate that although BAST has a clear legal basis under Indonesian construction and procurement regulations, the regulatory framework lacks detailed provisions regarding risk allocation, post-handover liability, and latent defects. NVivo analysis shows that ambiguity in post-handover responsibility is the most dominant issue. The study also identifies significant gaps between national practices and international standards such as FIDIC, particularly in defect notification periods and post-completion claims.Conclusions: The BAST clause primarily functions as an administrative document rather than a comprehensive legal instrument for risk management. Stronger contractual clarity is required to enhance legal certainty, accountability, and dispute prevention in public construction projects.Limitations: The study is limited to a single case and focuses on legal and contractual dimensions.Contributions: This research contributes to construction contract law by providing empirical evidence on legal gaps in BAST implementation and offering recommendations for improving contractual risk allocation in public infrastructure projects.